Altered keratinization and vitamin D metabolism may be key pathogenetic pathways in syndromic hidradenitis suppurativa: a novel whole exome sequencing approach. Issue 1 (July 2020) - Brandao, Lucas; Moura, Ronald; Tricarico, Paola Maura; Gratton, Rossella; Genovese, Giovanni; Moltrasio, Chiara; Garcovich, Simone; Boniotto, Michele; Crovella, Sergio; Marzano, Angelo Valerio
Highlights: Whole Exome Sequencing approach and novel bioinformatic pipeline has been adopted. 4 biological pathways are shared by all PASH and PAPASH patients. All pathways are related to biological processes involving the skin. The mainly impacted pathway is Vitamin D metabolism. All patients show low Vitamin D serum levels and its supplementation is envisaged. Abstract: Background: Diagnosis of pyoderma gangrenosum, acne and hidradenitis suppurativa (PASH) and pyogenic arthritis, pyoderma gangrenosum, acne, and hidradenitis suppurativa (PAPASH) patients, in spite of recently identified genetic variations, is just clinical, since most patients do not share the same mutations, and the mutations themselves are not informative of the biological pathways commonly disrupted in these patients. Objective: To reveal genetic changes more closely related to PASH and PAPASH etiopathogenesis, identifying novel common pathways involved in these diseases. Methods: Cohort study on PASH ( n = 4) and PAPASH ( n = 1) patients conducted using whole exome sequencing (WES) approach and a novel bioinformatic pipeline aimed at discovering potentially candidate genes selected from density mutations and involved in pathways relevant to the disease. Results: WES results showed that patients presented 90 genes carrying mutations with deleterious and/or damage impact: 12 genes were in common among the 5 patients and bared 237 ns ExonVar (54 and 183 in homozygosis and heterozygosis, respectively). In the pathway enrichment analysis, only 10 genes were included, allowing us to retrieve 4 pathways shared by all patients: (1) Vitamin D metabolism, (2) keratinization, (3) formation of the cornified envelope and (4) steroid metabolism. Interestingly, all patients had vitamin D levels lower than normal, with a mean value of 10 ng/mL. Conclusion: Our findings, through a novel strategy for analysing the genetic background of syndromic HS patients, suggested that vitamin D metabolism dysfunctions seem to be crucial in PASH and PAPASH pathogenesis. Based on low vitamin D serum levels, its supplementation is envisaged.